PERAN MEDIA SOSIAL SEBAGAI KATALISATOR KEPUTUSAN PEMBELIAN DIMSUM MENTAI DESAJI DI SIDOARJO - Aulia Rahmawati; Maisyatus Su'adaa Irfana; Anita Kartika Sari; Ririn Andriana (Ekomania, 2025)
This research highlights the role of social media as a catalyst in purchasing decisions for Dimsum Mentai Desaji products in Sidoarjo. By utilizing platforms such as Instagram and TikTok, Dimsum Mentai Desaji has succeeded in expanding its market reach and building close relationships with consumers. Through a descriptive qualitative approach based on case studies, data was obtained from in-depth interviews, observation of social media activities, and analysis of content documentation. The analysis results reveal that social media strategies, including attractive product visualization, customer testimonials, collaboration with influencers and active interaction with consumers, significantly influence purchasing decisions. Collaborations with influencers increase consumer trust and promotional reach, while testimonials strengthen social validation. Social media also plays a role in building brand trust and loyalty. This research concludes that social media not only functions as a communication tool, but is also the main catalyst in forming consumer trust, loyalty and purchasing decisions. Dimsum Mentai Desaji is advised to continue to innovate in social media strategies by increasing content creativity and maximizing interactive features in order to maintain competitiveness in the local culinary industry.